2012
DOI: 10.7314/apjcp.2012.13.10.5207
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Cell Proliferative Efficacy of Ferulic Acid Against 7, 12-dimethylbenz(a) Anthracene Induced Hamster Buccal Pouch Carcinogenesis

Abstract: The present study was designed to explore the anti-cell proliferative efficacy of ferulic acid by analysing the expression pattern of cell proliferative markers, proliferating cellular nuclear antigen (PCNA) and cyclin D1, in the buccal mucosa of golden Syrian hamsters treated with 7,12-dimethylbenz(a)anthracene (DMBA). Oral squamous cell carcinomas developed in the buccal pouch of hamsters using topical application of 0.5% DMBA three times a week for 14 weeks. Immunohistochemical (PCNA) and RT-PCR (Cyclin D1)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 30 publications
(20 reference statements)
0
10
0
Order By: Relevance
“…p-coumaric acid up-regulates CDKN1A (cyclin-dependent kinase inhibitor 1), CCNA2 (cyclin A2) and CCNB1 (cyclin B1) (Janicke et al 2011). In an in vivo inducible hamster buccal pouch carcinoma model, the oral administration of ferulic acid prevented cancer formation and down-regulated the expression of PCNA (proliferating cell nuclear antigen) and cyclin D1 (Prabhakar et al 2012). After inducing cell cycle arrest in the G0/G1 phase, chlorogenic acid (Fig.…”
Section: Cell Cycle Progression Inhibitorsmentioning
confidence: 99%
See 1 more Smart Citation
“…p-coumaric acid up-regulates CDKN1A (cyclin-dependent kinase inhibitor 1), CCNA2 (cyclin A2) and CCNB1 (cyclin B1) (Janicke et al 2011). In an in vivo inducible hamster buccal pouch carcinoma model, the oral administration of ferulic acid prevented cancer formation and down-regulated the expression of PCNA (proliferating cell nuclear antigen) and cyclin D1 (Prabhakar et al 2012). After inducing cell cycle arrest in the G0/G1 phase, chlorogenic acid (Fig.…”
Section: Cell Cycle Progression Inhibitorsmentioning
confidence: 99%
“…In an inducible oral tumor mouse model, ferulic acid (Fig. 1), a phenolic compound released during chlorogenic acid catabolism, decreased the expression of PCNA, an essential processivity factor of DNA replication (Prabhakar et al 2012).…”
Section: Immortalitymentioning
confidence: 99%
“…(Ligusticum) (8). FA exerts multiple biological activities such as antioxidant, and anti-inflammation (9,10) and it is known for treatment of Alzheimer's disease (11), cardiovascular disease (12), and cancer (13). In addition, FA is reported to have hepato-protective activity (14,15).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies from our laboratory have also shown the chemopreventive potential of ferulic acid against oral and mammary carcinogenesis [23,24]. Recently we have shown the proapoptotic and anti-cell proliferative efficacy of ferulic acid against DMBA induced hamster buccal pouch carcinogenesis [25,26]. The present study explores the anticell proliferative efficacy of ferulic acid against 7, 12dimethylbenz(a)anthracene inducing hamsters buccal pouch carcinogenesis.…”
Section: Introductionmentioning
confidence: 79%